2023
DOI: 10.3390/cancers15133475
|View full text |Cite
|
Sign up to set email alerts
|

True Prevalence of Unforeseen N2 Disease in NSCLC: A Systematic Review + Meta-Analysis

Abstract: Patients with unforeseen N2 (uN2) disease are traditionally considered to have an unfavorable prognosis. As preoperative and intraoperative mediastinal staging improved over time, the prevalence of uN2 changed. In this review, the current evidence on uN2 disease and its prevalence will be evaluated. A systematic literature search was performed to identify all studies or completed, published trials that included uN2 disease until 6 April 2023, without language restrictions. The Newcastle-Ottawa Scale (NOS) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 102 publications
0
2
0
Order By: Relevance
“…Although a conversion to a lobectomy is feasible if lymph node metastasis is detected intraoperatively, a completion lobectomy may pose technical difficulties in patients found to have occult lymph node metastasis after surgery. Recent studies investigating long-term outcomes in patients with an occult N2 after either a lobectomy or a segmentectomy have shown that the type of surgical procedure, either a lobectomy or a segmentectomy, does not significantly affect survival rates; instead, appropriate adjuvant chemotherapy plays a crucial role [40,41]. Therefore, emphasis should be placed on administering adequate adjuvant treatment based on proper staging to improve patient survival rates, rather than solely relying on completion lobectomies.…”
Section: Navigating the Success And Challenges Of Sublobar Resection:...mentioning
confidence: 99%
“…Although a conversion to a lobectomy is feasible if lymph node metastasis is detected intraoperatively, a completion lobectomy may pose technical difficulties in patients found to have occult lymph node metastasis after surgery. Recent studies investigating long-term outcomes in patients with an occult N2 after either a lobectomy or a segmentectomy have shown that the type of surgical procedure, either a lobectomy or a segmentectomy, does not significantly affect survival rates; instead, appropriate adjuvant chemotherapy plays a crucial role [40,41]. Therefore, emphasis should be placed on administering adequate adjuvant treatment based on proper staging to improve patient survival rates, rather than solely relying on completion lobectomies.…”
Section: Navigating the Success And Challenges Of Sublobar Resection:...mentioning
confidence: 99%
“…In the pre‐PET era, upstaging to pN2/3 was observed in up to 25% of patients with T1/2 N0 NSCLC 9 . Consistent use of PET results in reduced post‐operative upstaging to approximately 6%–9%, 8,10–13 though varies according to clinico‐radiologic factors, including tumour size >3 cm (rate unforeseen N2 21%–22% 8,10 ) and cN1 (rate unforeseen N2 17%–25% 14–17 ).…”
mentioning
confidence: 99%